2022
DOI: 10.1111/famp.12783
|View full text |Cite
|
Sign up to set email alerts
|

Couple variables predicting retention in a brief intervention and research

Abstract: Therapy is an effective form of treatment for couple distress; yet, research shows that 20%-60% of couples terminate treatment prematurely. Predictors of couple retention in therapy and research are unclear, particularly for couples from marginalized populations, which has important implications for the quality and generalizability of research results, and the benefits derived from therapy are limited when participants are not retained. The purpose of this study (N = 1310) was to identify couple-level

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Recent research has specifically examined variables associated with recruitment and retention rates in couple research. In a study of couple‐level variables associated with retention in a two‐session couple intervention and follow‐up research, findings showed that couples were less likely to be retained if at least one partner identified as Asian, Pacific Islander, Native American, or Hispanic (Mitchell et al, 2022). Further, a study on the transition to parenthood with ethnically minoritized couples with low‐income reported an 11% recruitment rate and a 36% retention rate in the intervention group (Baucom et al, 2018).…”
Section: Recruitment and Retention In Couple Researchmentioning
confidence: 99%
“…Recent research has specifically examined variables associated with recruitment and retention rates in couple research. In a study of couple‐level variables associated with retention in a two‐session couple intervention and follow‐up research, findings showed that couples were less likely to be retained if at least one partner identified as Asian, Pacific Islander, Native American, or Hispanic (Mitchell et al, 2022). Further, a study on the transition to parenthood with ethnically minoritized couples with low‐income reported an 11% recruitment rate and a 36% retention rate in the intervention group (Baucom et al, 2018).…”
Section: Recruitment and Retention In Couple Researchmentioning
confidence: 99%
“…More recently, studies have suggested RC may have secondary mental health benefits such as depression reductions up to 6 months after treatment (Cigrang et al, 2022; Gray et al, 2020; Mitchell et al, 2023). This reflects the benefits of longer‐form generic couple therapies seen for PTSD (Monson et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This issue of Family Process includes several papers related to evidence and the practice of couple and family therapy. In this editorial, I call attention to two papers by Lorås et al (2023); Whittaker et al (2023), and a special section in this issue focused on expanding the representativeness of research about couple therapy (Mitchell & Gordon, 2023).…”
mentioning
confidence: 99%
“…How, in fact, does one get to more inclusiveness in research (and more broadly in couple therapy itself)? Our special section features several papers that help imagine how inclusiveness can be expanded—some from examining efforts in the context of research (Mitchell et al, 2023; Whitton et al, 2023) and others from reimagining how to present couple intervention (Daire et al, 2023; Williamson et al, 2023). Certainly, it is an essential task to ask how to enable better recruitment and participation by a wider range of people in couple therapy research.…”
mentioning
confidence: 99%
See 1 more Smart Citation